Atención al cliente en el supermercado Dismero de la ciudad de Babahoyo - Moran Chica, Karen Daniela (2019)
The supermarket Dismero SA was created in 1996 as a small family business, has its headquarters in the city of Babahoyo and has 24 years in the market is dedicated to the commercialization of consumer products and is currently one of the most recognized supermarkets in the city; It maintains branches in Babahoyo, Jujan and Montalvo, which has allowed it to position itself in the market and in the minds of consumers. Customer satisfaction plays an essential role since the company's life depends on them, which is why this research is focused on making known the reasons why supermarket customers feel dissatisfied with the attention they receive from the staff that works there